PENGARUH LINGKUNGAN KERJA, DISIPLIN DAN MOTIVASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN BAGIAN PRODUKSI PT. SINAR SIAK DIAN PERMAI BANDAR SEKIJANG PELALAWAN - Thamrin, Edy; ', Machasin; ', Sjahruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was conducted at PT. Sinar Siak Dian Permai is located at 31 km East Cross street, District Bandar Sekijang, Pelalawan. The purpose of this study to determine how the workplace environment, work discipline and motivation affect the productivity of employees of PT. Sinar Siak Dian scenic. To find out which factor is the most powerful influence on employee productivity in PT. Sinar Siak Dian Permai. To achieve these objectives the research conducted using a sample of respondents totaled 137 people, using census method. Methods of data analysis using simultaneous test and the partial test. Based on the research results which indicate that there is a significant influence on the work environment, discipline and motivation on employee productivity.Based on the above calculation of the value obtained by the coefficient of determination (R2) of 0534.this suggests that the working environment, discipline and motivation simultaneously provide 46.6% of the effect on labor productivity in the production of PT. Sinar Siak Dian Permai Bandar Sekijang. Recommendations can be submitted is to PT.Sinar Siak Dian Permai that further enhance the work environment, discipline and motivation because these variables affect employee productivity which certainly have an impact on the performance of the employee in carrying out activities in the company.Keywords: work environment, discipline, motivsi and work productivity.